Research result HUMAS BIRO PEMBERITAAN DPR RI DALAM ANALISIS PEST - Veranus Sidharta; Irfan Fauzi (LPPM Universitas Bina Sarana Informatika, 2020)
The DPR RI as a legislative body whose members are directly elected by the people and have functions as maker, proposer, legislator, executive supervisor and APBN preparation are required to have a positive image in the eyes of the public. The role of public relations is indispensable in the relationship between institutions and the public, creating a good image for institutions and fostering positive and mutually beneficial relationships with the public. PEST analysis is used as a component to identify external forces on the influence of opportunity and threat factors on current conditions and situations by taking advantage of opportunities and anticipating threats from external institutions. The DPR RI institutionally has two characteristics which include temporary institutions and permanent institutions. Economic and Budget Policy, the DPR RI discusses and decides whether or not to approve a draft law on the State Budget, social factors include aspects related to the use of media in disseminating information while the technology factor covers aspects of information and communication technology in the form of access to availability data and information.